2010
DOI: 10.1093/cercor/bhq217
|View full text |Cite
|
Sign up to set email alerts
|

Primary Motor Cortex of the Parkinsonian Monkey: Differential Effects on the Spontaneous Activity of Pyramidal Tract-Type Neurons

Abstract: Dysfunction of primary motor cortex (M1) is thought to contribute to the pathophysiology of parkinsonism. What specific aspects of M1 function are abnormal remains uncertain, however. Moreover, few models consider the possibility that distinct cortical neuron subtypes may be affected differently. Those questions were addressed by studying the resting activity of intratelencephalic-type corticostriatal neurons (CSNs) and distant-projecting lamina 5b pyramidal-tract type neurons (PTNs) in the macaque M1 before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
150
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(174 citation statements)
references
References 135 publications
(242 reference statements)
18
150
6
Order By: Relevance
“…We measured the fraction of power allocated in the 8-30-Hz band for each PYN and we found that this fraction increased in 331 out of 600 PYNs when under PD conditions, which is consistent with the increment of oscillations in that band reported by ref. 76. The average increment in the 8-30 Hz power across these 331 PYNs was 5.9 ± 6.0% (mean ± SD, range: 0-53.9%) and resulted in no prominent oscillation in that band, which is consistent with the analysis of single unit recordings of MPTP-treated NHPs reported in ref.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We measured the fraction of power allocated in the 8-30-Hz band for each PYN and we found that this fraction increased in 331 out of 600 PYNs when under PD conditions, which is consistent with the increment of oscillations in that band reported by ref. 76. The average increment in the 8-30 Hz power across these 331 PYNs was 5.9 ± 6.0% (mean ± SD, range: 0-53.9%) and resulted in no prominent oscillation in that band, which is consistent with the analysis of single unit recordings of MPTP-treated NHPs reported in ref.…”
Section: Resultssupporting
confidence: 89%
“…In cortex, the percentage of PYNs with random, regular, or bursty patterns mildly changed at the transition from normal to PD conditions (random: 270 vs. 290; regular: 97 vs. 121; bursty: 231 vs. 184; normal vs. PD; definition of the patterns is given in ref. 76 and SI Note 4), and nonsignificant changes (Wilcoxon rank-sum test, P > 0:05) were reported for the distribution of the firing rates across the PYNs (Fig. 4 A, B, D, and E), the population-average firing rate (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Among these, abnormal bursting and oscillatory fluctuations of neuronal discharge are particularly noticeable [147][148][149][150][151][152]. Oscillatory activity can be identified in electrophysiological recordings of the activity of single neurons in GPi, SNr, STN, and MC in animals and patients with PD [153]. The proportion of cells in STN and GPi that discharge in bursts is also greatly increased in parkinsonism [143,144,152,154,155].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%
“…In contrast, interventions directed at the PPN have revealed significant motoric effects in animal experiments [55]. Thus, PPN inactivation in normal primates reduces body movements of arms, trunk, and legs [142][143][144][145][146], and PPN injection of a GABA-A receptor antagonist, or low-frequency stimulation of PPN, alleviates experimental akinesia in monkeys, presumably by increasing PPN activity [146][147][148][149][150][151][152][153][154][155][156]. This constellation of findings suggests the possibility that the descending basal ganglia projections to the brainstem may play a greater role in the pathophysiology of akinesia/bradykinesia and movement than is commonly assumed.…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%